Reconsidering Durkheim's Assessment of Tarde: Formalizing a Tardian Theory of Imitation, Contagion, and Suicide Suggestion1. Issue 3 (September 2014) - Abrutyn, Seth; Mueller, Anna S.
<x xml:space="preserve">Abstract</x> Emile Durkheim summarily rejected Gabriel Tarde's imitation thesis, arguing that sociology need only concern itself with social suicide rates. Over a century later, a burgeoning body of suicide research has challenged Durkheim's claim to a general theory of suicide as 4 decades worth of evidence has firmly established that (1) there is a positive association between the publicization of celebrity suicides and a spike in the aggregate suicide rate, (2) some social environments are conducive to epidemic‐like outbreaks of suicides, and (3) suicidal ideas or behavior spreads to some individuals exposed to a personal role model's suicidal behavior—for example, a friend or family member. Revisiting Tarde, the article examines why Tarde's theory deserves renewed attention, elucidates what he meant by imitation, and then formalizes his "laws" into testable theses, while suggesting future research questions that would advance the study of suicide, as well as other pathologies. Each "law" is elaborated by considering advances in contemporary social psychology as well as in light of its ability to supplement Durkheim's theory in explaining the "outlier" cases.